Science communication for social inclusion: exploring science & art approaches - Matias, Ana (2021)
Engaging communities at risk of social exclusion poses a big challenge for science communicators. We schematize a framework for projects using science & art to promote social inclusion, composed of 3 phases — design, plan and collaboration; implementation; and evaluation. We present a case study that aimed to engage with a community of migrant senior women, mostly illiterate. Our findings suggest high engagement was achieved by building trust, involving emotions, choosing a relatable topic and following participatory practices. Inclusive activities occurred on the short-term, but for medium-term impact, community insiders need to be regarded as a second audience.